Breast Thickness in Routine Mammogram - Shareef, Najlaa R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this study was to evaluate the thickness of the compressed breast in mediolateral oblique (MLO) and craniocaudal (cc) mammograms to relate these thickness and breast patterns to mean glandular dose (MAD) in Iraqi women and to evalualat radiology’s recommendation for Iraqi women. The study of population consists of 20 paired MLO and CC mammograms obtained on one mammograms unit .The digital read out of compressed breast thickness MGD was calculated by multiplying entrance skin exposure by the exposureto-absorbed dose conversion factor for the range of breast thickness which was 7.1 —-7.4cm in cc mammograms with a mean breast thickness of 7.2 cm and 7.3 ——7.5 cm in MLO mammograms with a mean breast thickness of 7.52 MGDs in cc and MLO mammograms were 1.89 mGY and 1.99 mGY per view respectively. According to our initial trial, the MGDS OF IRAQI women are lower than recommended by the American collage and UK of radiology.